Bacterial profile of bovine mastitis in Ethiopia: a systematic review and meta-analysis - Tora,Ephrem Toma; Bekele,Nahom Belay; Suresh Kumar,R. S. (PeerJ, 2022)
Background Bovine mastitis is the commonest episode of infection in the dairy industry, which often occurs after damage of epithelial cells lining the teat duct. It is ranked as the second most important cause of milk production loss directly and a devastating disease with a higher incidence leading to the culling of dairy cows. Thus, this systematic review and meta-analysis is aimed to quantitatively estimate the current status of mastitis in general and bacterial mastitis particular in Ethiopia. Methods A literature search was carried from major databases and indexing services including PubMed, Google Scholar, Science Direct. Also, local institution repositories were searched to retrieve unpublished MSc and PhD theses. All studies were included addressing the prevalence of mastitis and bacterial isolates conducted in Ethiopia. Microsoft Excel was used to extract data and was imported to R Studio for the analyses. The random-effects model at a 95% confidence level was used for pooled estimates of outcomes. The degree of heterogeneity was computed by Higgins’s I2 statistics. Publication bias was checked by using the funnel plots of standard error augmented by Begg’s and Egger’s tests. Results A total of 46 studies with 15,780 cows were included in this study. All studies have collected 18,478 suspected samples for bacterial isolation. While pooled prevalence estimate of mastitis was 47.6%, the bacterial isolates pooled prevalence was 33.1%. The bacterial mastitis was 6.5% in cows infected by clinical patients and was 28.3% subclinical patients. The common isolates were Staph aureus, Strep species, Staph epidermis, Escherchia coli, Corynebacterium bovis, Coagulase Negative Staphylococcus and Klebsiella species. A univariate meta-regression analysis evidenced that the type of mastitis and management system was a possible source of heterogeneity (P-value = 0.001). Conclusion The pooled prevalence of bacterial mastitis in Ethiopian dairy cattle was high. The analysis showed bacterial pathogens like Staphylococcus aureus, Staph epidermis, Strep species and Coagulase Negative Staphylococcus are majorly accounted for bovine mastitis in Ethiopia. Therefore, the highly prevalent and commonly isolated pathogens cause contagious mastitis which require immediate attention by dairy producers to put under control by devising robust mastitis prevention and control interventions.
Keywords: Bacterial isolates; Bovine; Mastitis; Ethiopia; Systematic review; Meta-analysis